The importance of scientists’ intellectual humility for communicating effectively across ideological and identity-based divides - Kimberly Rios; Zachary C. Roth; Thomas J. Coleman (Proceedings of the National Academy of Sciences, 2025)
Growing identity-based and partisan gaps in confidence in scientists and scientific institutions call for novel approaches to science communication. In this perspectives piece, we focus on the need for greater intellectual humility (i.e., willingness to revise one’s views and admit that one might be wrong) among social scientists, who are met with particularly high levels of skepticism from the public. We begin with an overview of research demonstrating that when scientists’ identities or ideologies align (or are perceived to align) with those of the public, trust in science increases. We then highlight intellectual humility as a potential tool for cultivating trust in the social sciences even when social scientists’ and the public’s identities or ideologies do not match. Specifically, intellectual humility among social scientists predicts less bias toward one another’s research and hence may increase the diversity of perspectives to which the public is exposed and shift public perceptions of social scientists. We conclude with a discussion of how to foster intellectual humility in science communication, broadly defined.